Phase separation in pyrex glass by hydrothermal treatment: evidence from micro-Raman spectroscopy - Sigoli, F. A.; Kawano, Y.; Davolos, Marian Rosaly [UNESP]; Jafelicci, M. (Elsevier B.V., 2001)
In this work, we investigated the formation of porous silica matrix obtained by hydrothermal treatment under saturated steam condition from Pyrex (R) glass. This investigation was carried out by scanning electron microscopy (SEM), infrared spectroscopy (IR), X-ray powder diffractometry (XRD) and Raman microscopy. We observed the presence of connected and homogeneously distributed pores in a non-crystalline silica phase and a detectable interface between silica and remnant glass phases resulting in a framework similar to asymmetric membranes. The results indicate that the process of phase separation takes place at lower temperature than that of glass-transition on the surface of the glass phase. Essential reaction between water and silica at supercritical condition together with the formation and leaching of soluble phase contribute to obtain porous silica matrix, (C) 2001 Elsevier B.V. B.V. All rights reserved.